The Role of Strategic Awareness in Achieving Strategic Leadership: AnAnalytical Study of the Opinions of College Council Members in a Sample of Private Universities in the city of Erbil - Kurdistan Region of Iraq - Ibrahim Wali, Ahlam; Salah Abid, Kalsum (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
The aim of the research is to analyze the relationship and impact of the strategic awareness variable in private universities, represented by its dimensions (internal strategic awareness, external strategic awareness), in the dimensions of strategic leadership represented by (creativity, competitive advantage, and risk tolerance). The general framework of the research is represented by the problem of the study, which identified by raising several questions about the nature of the relationship and influence between the independent variable (strategic awareness) and the dependent variable (strategic leadership). Multiple questionnaires were used as the main tool for data acquisition. The research followed the descriptive analytical approach, as the main and sub-variables were described, as well as the analysis of relationships and influence between the variables, representing the research community in all the private universities in the city of Erbil, the Kurdistan Region of Iraq, which numbered (9) universities. The sample was represented by (7) universities, and the respondents were (85) members of the college councils in the selected sample of universities. The hypotheses were tested through a set of statistical tests using the computer program (SPSS V.23). The research reached a set of conclusions, the most important of which is the existence of high correlations and strong influences between the main and sub-variables, at the macro and micro levels, and the correlation was high between external awareness and creativity, while the influence of external awareness was strong in strategic leadership. The research suggested a set of proposals in the light of the conclusions, including the necessity of harnessing the strong relations between the two variables and their orientation towards serving the researched universities with the need to strengthen the relationship between internal awareness and risk tolerance and serious endeavor to support weak relations.